1999
DOI: 10.1063/1.369459
|View full text |Cite
|
Sign up to set email alerts
|

Electrical response during indentation of piezoelectric materials: A new method for material characterization

Abstract: Triple-point-type morphotropic phase boundary based large piezoelectric Pb-free material-Ba(Ti0.8Hf0.2)O3-(Ba0.7Ca0.3)TiO3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 12 publications
5
35
1
Order By: Relevance
“…electrically conducting vs insulating). Good agreement was found between the experimental results and predictions of an analytical model of Giannakopoulos and Suresh (1999) for the spherical indentation of a transversely isotropic piezoelectric material. A parametric analysis was conducted to identify key material properties that in¯uence the indentation response.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…electrically conducting vs insulating). Good agreement was found between the experimental results and predictions of an analytical model of Giannakopoulos and Suresh (1999) for the spherical indentation of a transversely isotropic piezoelectric material. A parametric analysis was conducted to identify key material properties that in¯uence the indentation response.…”
supporting
confidence: 65%
“…Complimentary investigations into the electrical response during indentation of piezoelectric solid are reported elsewhere [13], where the indentation force vs the electric charge induced in the indentor were measured continuously by using a conducting steel sphere with a zero bias. These companion studies [13] in conjunction with the present work show that, by using instrumented indentation, the poling direction, the aging response, and some material properties can be determined. This paper is organized in the following manner.…”
Section: Introductionmentioning
confidence: 99%
“…We measured piezoelectric properties of polycrystalline sample of a-PbO 2 -like silica synthesised at 82(2) GPa and 950(25) K and subsequently decompressed to ambient conditions. Indentation technique [19] was used. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This work shows that the functional relationship between the load, P, and the depth of penetration, h, does not get altered because of electromechanical coupling; i.e., P / h 1.5 for spherical indentation of elastic solid remains valid. However, the indentation stiffness (the proportionality constant, S, in P = Sh 1.5 ) depends on the condition of material (poled versus unpoled) as well as the electrical nature of the indenter (conducting versus insulating), which was experimentally verified by Ramamurty et al 20 Similarly, predictions on the electrical response were confirmed by Sridhar et al 21 Makagon et al 10 have performed indentation experiments using spherical and conical indenters. Their study indicates that the contact stiffness is weakly affected by the piezoelectric coupling.…”
Section: Introductionmentioning
confidence: 53%